Peran Self-Regulated Learning Sebagai Mediator Pada Hubungan Mastery Goal Orientation Dengan Tanggung Jawab Belajar Mahasiswa Di Kota Surabaya - Ashfanul Kholiqin; Wiwik Juwarini Prihastiwi; Dzulkifli (Universitas Muhammadiyah Gresik, 2026)
Background: Learning responsibility is an important personality characteristic for students, as it has an impact on academic achievement. However, in reality, many university students still demonstrate low levels of learning responsibility. Objective: This study aims to examine the effect of mastery goal orientation on learning responsibility through self-regulated learning as a mediator among university students in Surabaya. Method: The participants in this study were 384 university students in Surabaya. Data were collected using Likert-scale instruments measuring mastery goal orientation, self-regulated learning, and learning responsibility. Data were analyzed using path analysis. Results: The results of the path analysis indicated a significant relationship between mastery goal orientation and self-regulated learning (p < 0.05); a significant relationship between mastery goal orientation and learning responsibility (p < 0.05); and a significant relationship between self-regulated learning and learning responsibility (p < 0.05). Hypothesis testing using the Sobel test yielded a calculated t-value of 2.77, which was greater than the critical t-value (2.77 > 1.96) at a significance level of 0.05. Conclusion: Therefore, it can be concluded that self- regulated learning mediates the relationship between mastery goal orientation and learning responsibility.